Patternmaking for fashion design - Armstrong, Helen Joseph (Pearson Education Limited, 2014)
For an undergraduate course in Patternmaking. Renowned for its comprehensive coverage, exceptional illustrations, and clear instructions, this #1 text offers detailed yet easy-to-understand explanations of the essence of patternmaking. Hinging on a recurring theme that all designs are based on one or more of the three major patternmaking and design principles-dart manipulation, added fullness, and contouring-it provides students with all the relevant information necessary to create design patterns with accuracy regardless of their complexity. Some innovative, new information in this book include: Updated with modern, cutting-edge sketches and designs. Ribbing added to the knit section of Chapter 27. More materials on children's wear and swim wear. Knock offs. Fitting corrections Advanced design projects A practical introduction to patternmaking Complete coverage of the three steps of design patterns: dart manipulation, added fullness, and contouring. Chapter projects